The insider’s guide to 52 homes in 52 weeks : - Roos, Dolf de (John Wiley & Sons, 2006)
A real estate guide unlike any other, The Insider's Guide to 52 Homes in 52 Weeks is the true story of a seemingly impossible investing challenge and the two investors who pulled it off--all to prove that you can do it too.